Automated street light system by using wireless sensor networks - Alhanouf Alburaikan (Computational Algorithms and Numerical Dimensions)
Consumption of power is essential for the sustainability of future generations. The constant developing world makes everyone run beyond the capabilities and to meet the needs of the growing world. Conservation of electricity is the least concern of the today’s man. Concern to this problem, automated street light system can play a part in the electricity guard. The street light is combined with Light Dependent Resistor (LDR) to make it automatically identifying the range of visible light and perform decision making whether to turn on or turn off the light.